2017
DOI: 10.1002/2016ja023684
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐biennial oscillation of the ionospheric wind dynamo

Abstract: The interannual variation of the ionospheric solar quiet (Sq) current system is examined. A dense magnetometer network over Japan enables the accurate determination of the central position of the northern Sq current loop or the Sq current focus, during 1999–2015. It is found that the Sq focus latitude undergoes an interannual variation of ±2° with a period of approximately 28 months, similar to the quasi‐biennial oscillation (QBO) in the tropical lower stratosphere. The QBO‐like variation of Sq is particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 73 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…The anomaly Δ V Z , shown in Figure a, was calculated as the deviation of V Z (black line in Figure a) from the seasonal solar cycle climatology (green dashed line in Figure a). Following Yamazaki et al (), a moving average with a 13‐month window was applied to Δ V Z in order to extract the variation on time scales longer than a year. The results, shown in Figure a (red line), reveal an interannual variation of ∼2 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The anomaly Δ V Z , shown in Figure a, was calculated as the deviation of V Z (black line in Figure a) from the seasonal solar cycle climatology (green dashed line in Figure a). Following Yamazaki et al (), a moving average with a 13‐month window was applied to Δ V Z in order to extract the variation on time scales longer than a year. The results, shown in Figure a (red line), reveal an interannual variation of ∼2 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…The interannual variability of upward propagating tides is due in part to the interannual variability of the background atmosphere, through which the tidal waves propagate (Mayr & Mengel, ; McLandress, ). Some identified sources of the interannual variability of tides include the QBO in the stratosphere (Liu, ; Yamazaki et al, ) and the El Niño–Southern Oscillation (ENSO) in the troposphere (Liu et al, ; Pedatella & Liu, ; ). The QBO has a regular oscillation cycle of ∼28 months, while ENSO consists of longer‐period oscillations (∼43 and ∼62 months) (Liu, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of electron density measurements from the Challenging Microsatellite Payload (CHAMP) and the Gravity Recovery and Climate Experiment (GRACE) satellites during the 2000–2014 period by Zhou et al () found evidence for a QBO modulation of the low‐latitude DE3 feature but did not find evidence for any QBO modulation of nonmigrating features at midlatitudes. Yamazaki et al () found a QBO‐like variation in the northern ionospheric current loop observations during solar minimum (when apparent solar QBO variations are not present), which they attributed to QBO modulation of DW1, DE3, and SW2 modes based on a series of whole atmosphere model experiments with constrained meteorology below 30‐km altitude. However, the results of this study could not identify which tidal modes were most important for producing the observed QBO variations.…”
Section: Interseasonal Variabilitymentioning
confidence: 99%